Kyivan iconography of St. Nicholas of Myra-Lycia and the icon of St Nicholas the Wet from Saint Sophia Cathedral - Tetiana Lіuta (Київські історичні студії)
The history of the study of the Old Rus iconographic heritage of Kyiv is an extremely small contribution to the national history of art. Until now, Russian scholars with their biased attitude toward Ukrainian, and primarily Kyivan, iconographic sources, which were mostly stolen and appropriated by Moscow museums, have been leading the way in this research. Such an illustrative monument is the fresco of St Nicholas from St Michael’s Golden-Domed Cathedral, which is now kept in the Tretyakov Gallery. The purpose of the article is to clarify the attribution and search for the famous icon of St. Nicholas the Wet from Saint Sophia Cathedral in Kyiv. The research methods used were source and comparative methods of studying iconographic monuments. In ancient times, there was no icon of the so-called Nicholas the Wet in Saint Sophia Cathedral. Its appearance there dates back to the time of Metropolitan Petro Mohyla. The original icon was brought to the All-Ukrainian Museum Campus in 1934 for photographic fixation and restoration, after which it was in the collection of the National Art Museum of Ukraine. After the Second World War, the icon was recorded in an act with the corresponding code of the same museum, but today the fate of the rarity is unknown. We can state a special ancient Kyivan tradition of venerating St Nicholas of Myra-Lycia, which, in addition to written monuments dedicated to the miracles of the saint, was clearly manifested in his iconography. Kyivan mosaics, frescoes, and icons depicting the saint are characterized by a wealth of artistic forms and psychological techniques, but they convey the ancient Byzantine common.